Facile synthesis of self-aligned gold nanoparticles by crack templated reduction lithography. Issue 22 (27th February 2017) - Lim, Min-Cheol; Kim, Sae-Hyung; Park, Kisang; Kim, Young-Rok; Kim, Jae-Ho; Ok, Gyeongsik; Choi, Sung-Wook
Abstract : Crack templated reduction lithography for the facile synthesis of self-aligned gold nanoparticles. Abstract : Fabrication of 1D gold nanoparticle (NP) arrays by crack templated reduction lithography (CTRL) is demonstrated. The gold NPs are synthesized in situ on the cracks in a polydimethoxysiloxane (PDMS) substrate without additional reducing/stabilizing agents. Upon directionally bending the substrate, various array patterns formed on the PDMS rubber.